Analisis Computational Fluid Dynamic (CFD) Pengaruh Overlap Ratio dan Jarak Bilah Berlapis pada Kinerja Turbin Angin Savonius Bilah Berlapis - David, Jerico; Fahrudin, Fahrudin; Rhakasywi, Damora (ROTASI, 2024)
Abstract  The demand for energy is increasing, therefore researchers are utilizing alternative energy sources such as wind energy. Savonius is a type of vertical axis wind turbine (VAWT) that is suitable for use in low wind speed conditions, making it capable of operating in urban areas. Researchers are conducting extensive studies to improve the performance of Savonius wind turbines. The Savonius wind turbine used is a Savonius wind turbine with added layered blades. This research was conducted using the computational fluid dynamics (CFD) simulation method with an existing layered Savonius wind turbine model and varied the overlap ratio and the distance between the layered blades to determine the impact of these variations on efficiency improvement using Ansys Fluent 2022 R2 software. The variations in this study included an overlap ratio of 10% with a blade distance of 33 mm and an overlap ratio of 15% with blade distances of 22 mm and 33 mm at a wind speed of 6.46 m/s. The results showed that the layered Savonius wind turbine from previous research with a configuration of a 10% overlap ratio and a blade distance of 22 mm had the best performance with a power coefficient (Cp) of 0.173 and a torque coefficient (Ct) of 0.46. The results of this study provide an understanding of the impact of increasing the value of the layered blade distance and the overlap ratio on the performance of the Savonius wind turbine, which, if not appropriate, can reduce its efficiency. Keywords: wind energy, Savonius wind turbine, layered blades, overlap ratio, distance between layered blades